Investigating the implementation of Character Education in an Indonesian EFL Classroom - Siti Rochmatul Mu'alimah; Mukminatus Zuhriyah; Ria Kamilah Agustina (Universitas Islam Negeri (UIN) Mataram, 2020)
Character education has been central to the Indonesian education system due to promote outstanding generations as the building block of the nation’s future. Anchored in the concept of character education, this study aimed to investigate the extent to which the concept was implemented at an Indonesian Senior Secondary private school in terms of the types of character education and the methods employed by the English teachers in the school. This mixed method research collected the data from the English teachers teaching English at the eighth grade through interviews and documentation of their lesson plans and students’ textbook. The data were analyzed based on the Miles and Huberman data analysis procedure. The results demonstrate that the implementation of the character education performed by the English teachers was overall optimally implemented given the percentage of 87.5%. Another finding also evidenced that the types of character education incorporated by the English teachers referred to self-potential and religious value based character education, while the methods they employed were exemplary method, habituation, story method and reflection